Parhyale hawaiensis: a regeneration model and its viability as a chronic endpoint in ecotoxicology - Diehl, Otavio Jurgensen; Umbuzeiro, Gisela de Aragao; Assano, Patrícia Kushima (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Parhyale hawaiensis is a marine amphipod of circumtropical distribution and has been used in acute ecotoxicological tests. However, sub lethal responses are important endpoints in ecotoxicology because they allow the assessment of effects at environmental concentrations. P. hawaiensis has the ability to regenerate its appendages, limbs and tissues after an injury or loss during their entire life. Data on effects of toxicants on appendages regeneration of marine organisms are still scarce. Regeneration can be used as an ecotoxicological endpoint to assess potential teratogenic compounds and their impact on stem cells. Thus, the aim of this study was to obtain data on regeneration of antennae of P. hawaiensis to determine the viability this endpoint on toxicity tests.